Comparative Analysis of Criminal Act Regulations Relating to Freedom of Opinion During Demonstrations According to the New Criminal Code and Law No. 9 of 1998 concerning Freedom to Express Opinions in Public - Saputra, Muhammad Fajri; Yustrisia, Lola (Universitas Ibn Khaldun Bogor, 2024)
Human rights are rights that human beings have that have been acquired and carried along with their birth or presence in community life. It is considered that some of these rights are possessed without distinction on the basis of race, race, religion, or sex, and are therefore fundamental and universal. The law also regulates this right and it is also regulated about the right to freedom of opinion precisely in the criminal code and Law No. 9 of 1998 concerning the freedom to express opinions in public. The formulation of the problem of this study is to determine the characteristics of criminal acts related to freedom of opinion during protests in the new Criminal Code and also in Law No. 9 of 1998, as well as to compare the regulations on the two legal products regarding criminal acts related to freedom of opinion during protests. The nature of this research is descriptive, the approach used in this study is a normative juridical approach. From this study, results were found about criminal acts related to freedom of expression during protests and how they compare to existing laws.